THE PROBLEM ASPECTS AND TASKS OF THE AUDIT OF LABOR CALCULATIONS - Kravchenko, Mykola; Khil, Tatyana (Sworld-Us Conference proceedings, 2022)
The purpose of the article is to study the problem areas of accounting and audit of labor remuneration and identify directions for their improvement. For a complete understanding of this process, the role of wages is substantiated and its definition is gi